1996
DOI: 10.1002/(sici)1097-4628(19961205)62:10<1753::aid-app29>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymer architecture on the efficiency of acyl transfer reactions

Abstract: A series of spacer-modified polystyrene-supported hydroxamic esters and hydroxamic dithiocarbonic anhydrides were prepared starting from divinyl benzene and ethyleneglycol dimethacrylate crosslinked polystyrene resins through multistage polymer-analogous reactions. Acyl transfer reactions using these polymer-supported hydroxamic acylating agents containing spacer arms of various lengths were carried out. The investigation revealed a sharp increase in reactivity as the length of the spacer arm was increased fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recently polymer bound nucleophiles (anions) have been employed for a number of organic conversions [5][6][7] like alkylation, arylation, sulphonation, oxidation, aldol condensation and thiocyanation. Recently polymer bound nucleophiles (anions) have been employed for a number of organic conversions [5][6][7] like alkylation, arylation, sulphonation, oxidation, aldol condensation and thiocyanation.…”
Section: Regio-selective Formation Of O-acyl/o-benzoyl Hydroxamates Bmentioning
confidence: 99%
“…Recently polymer bound nucleophiles (anions) have been employed for a number of organic conversions [5][6][7] like alkylation, arylation, sulphonation, oxidation, aldol condensation and thiocyanation. Recently polymer bound nucleophiles (anions) have been employed for a number of organic conversions [5][6][7] like alkylation, arylation, sulphonation, oxidation, aldol condensation and thiocyanation.…”
Section: Regio-selective Formation Of O-acyl/o-benzoyl Hydroxamates Bmentioning
confidence: 99%
“…Investigations with various polymeric reagents have revealed that nature of the polymeric backbone does influence the kinetics and extent of functional group conversion in polymer-aided reactions (Morawetz 1978(Morawetz , 1985. The binding of a functional group to a polymer chain generally results in a new reagent with different structure, reactivity and selectivity (George and Pillai 1988;Sreekumar and Pillai 1989;Sudhakaran and Pillai 1990;Sophiamma and Sreekumar 1997).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The poly(hydroxamic acid) resin has potential commercial importance with the knowledge that hydroxamic groups are able to form complexes with wide range of metal ions. [3][4][5] Such a resin can be used for the recovery of heavy metals from aqueous media and uranium extraction from seawater. 6,7 A characteric feature of the chelating resins is the preservation of their high selectivity with respect to individual ions in the presence of large quantities of other ions.…”
mentioning
confidence: 99%